Entrepreneurial intention of university students: a comparison among undergraduate students of Nigerian universities - Bularafa, Bukar Ali; Abdullah, Abdul Rashid (Research Publishing Academy, 2019)
Due to the persistent increase in unemployment among university graduates. Entrepreneurship today is beyond just opportunity, but a necessity. The aim of this study is to determine and compare the level of entrepreneurial intention among undergraduate students of Abubakar Tafawa Balewa University (ATBU) Bauchi, Modibbo Adama University of Technology (MAUTECH) Yola and the University of Maiduguri in North-eastern, Nigeria. The study used survey research by means of a questionnaire. A sample of 383 students was chosen from the population of 3024. Data were analysed by means of descriptive statistics and Analysis of variance (ANOVA). The findings of the study indicate on average a significantly high level of intentions towards entrepreneurship among the university students, except students for the University of Maiduguri which showed low entrepreneurial intention. The findings further indicates differences between students of the University of Maiduguri and students of ATBU Bauchi and MAUTECH Yola, but no significant differences observed between students of ATBU Bauchi and MAUTECH Yola at .05 level. However, it is recommended there is need to encourage university graduates to consider entrepreneurship as a career instead of relying on government and the private sector for a job. Furthermore, further studies need to conduct on the role of culture on entrepreneurial intentions.